PENGARUH PENGGUNAAN MEDIA LEAFLET DAN VIDEO TERHADAP PENGETAHUAN REMAJA PUTRI TENTANG VULVA HYGINE SAAT MENSTRUASI DI SMP DHARMA SISWA KOTA TANGERANG - Yasmin Alhusna Salsabila; Rizki İsfahani and Ayu Pratiwi (Nusantara Hasana Journal, 2022)
Survey data conducted by the World Health Organization (WHO) in several countries, adolescent girls aged 10-14 years have problems with their reproduction. Maintaining the cleanliness of the female organs is very important, especially during menstruation. One solution is to provide counseling through the right media, including leaflets and videos. This study aims to determine the effect of using leaflets and videos on the knowledge of adolescent girls about vulva hygine during menstruation at Dharma Siswa Junior High School Tangerang City. This quasi-experimental study used a pre-test-post-test control group design. The sample size of this study was 72 with purposive sampling. Data analysis using parametric paired sample t-test and Independent T-Test, which were previously tested for normality and homogeneity. There is an effect before and after the use of leaflet media (p value = 0.000) and video media (p value = 0.000), and there is a difference after using leaflet and video media (p value = 0.000) on the knowledge of adolescent girls about vulvar hygiene when menstruation. There are differences in the use of leaflet and video media on the knowledge of adolescent girls about vulvar hygiene during menstruation.